2017
DOI: 10.1002/cne.24280
|View full text |Cite
|
Sign up to set email alerts
|

Cortical inter‐hemispheric circuits for multimodal vocal learning in songbirds

Abstract: Vocal learning in songbirds and humans is strongly influenced by social interactions based on sensory inputs from several modalities. Songbird vocal learning is mediated by cortico-basal ganglia circuits that include the SHELL region of lateral magnocellular nucleus of the anterior nidopallium (LMAN), but little is known concerning neural pathways that could integrate multimodal sensory information with SHELL circuitry. In addition, cortical pathways that mediate the precise coordination between hemispheres re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 127 publications
(283 reference statements)
8
53
1
Order By: Relevance
“…AId receives topographic input from parallel circuits that process auditory, visual, and somatosensory information, so a similar mechanism to link different neuronal subpopulations within AId would be advantageous for facilitating sensorimotor integration across modalities (Zeier and Karten, 1971;Bottjer et al, 2000;Paterson and Bottjer, 2017).…”
Section: Heterogeneous Activity Within Aid Suggests Multi-dimensionalmentioning
confidence: 99%
See 1 more Smart Citation
“…AId receives topographic input from parallel circuits that process auditory, visual, and somatosensory information, so a similar mechanism to link different neuronal subpopulations within AId would be advantageous for facilitating sensorimotor integration across modalities (Zeier and Karten, 1971;Bottjer et al, 2000;Paterson and Bottjer, 2017).…”
Section: Heterogeneous Activity Within Aid Suggests Multi-dimensionalmentioning
confidence: 99%
“…In songbirds, the cortical region AId lies within an area that has been considered to be analogous to motor cortex in mammals: akin to infragranular layers of mammalian motor cortex, AId receives inputs that process multi-modal sensory information via dNCL (dorsal caudolateral nidopallium) as well as information from corticobasal ganglia circuitry that is dedicated to vocal learning, and in turn makes a variety of projections that give rise to feedforward and feedback pathways through subcortical and brainstem regions ( Fig. 1A) (Zeier and Karten, 1971;Bottjer et al, 2000;Karten, 2013;Paterson and Bottjer, 2017). Lesions of AId in juvenile zebra finches impair the bird's ability to achieve an accurate imitation of its memorized tutor song but do not induce vocal motor deficits (Bottjer and Altenau, 2010), suggesting an important role for this region in guiding motor refinement during sensorimotor learning.…”
Section: Introductionmentioning
confidence: 99%
“…Mammals, however, evolved a highly topographic six-layered neocortex that recapitulates the peripheral sensory maps via point-to-point connections with subcortical regions (5)(6)(7). Moreover, the left and right cortical hemispheres of mammals are heavily interconnected compared with fewer such connections in birds, in which sensory-motor and associative regions of the telencephalic pallium receive limited input from the contralateral hemisphere (8,9) (Fig. 1).…”
mentioning
confidence: 99%
“…Consistent with this notion, it has recently been shown that precise homotopic wiring of the CC in the postnatal rodent brain requires preexisting functional homotopy (29). It is therefore plausible that ancestral pathways such as the anterior commissure (30) or symmetrical ascending bilateral inputs (13) are sufficient to provide the balance of interhemispheric integration and specialization required for complex multimodal cognition. The ability to conduct longitudinal investigations during a short sensitive period for vocal development makes the zebra finch an ideal model organism for investigating the behavioral relevance of this balance, allowing experimental manipulations not possible in humans.…”
Section: Discussionmentioning
confidence: 87%